Information technologies: socio-cultural aspect - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article is devoted to the study of the socio-cultural aspect of intellectual information technologies. Creation of the newest technolo-gies allows to improve mechanisms of management of social processes and increase the level of welfare of the society. The use of the information space for work, education, study and leisure leads to the emergence of new forms of intercultural interaction and not always to the desired changes in the cultural space of the information society.